A Comparative Study of Factors Affecting Family Well-Being of Single-Father and Single-Mother Families - Yujongdee, Benjarat; Thayansin, Sawitri; Khajornchaikul, Piyathida (Journal of Population and Social Studies [JPSS], 2025)
Single-father and single-mother families are unique family structures that face challenges in adapting to life situations. Family well-being is a critical factor in the developmental outcomes of children in these households. This study examined and compared family well-being levels in single-father and single-mother families, and analyzed the influence of demographic, familial, environmental, and work-life factors. The sample consisted of 406 single parents with children aged 0–12 years, comprising 105 single fathers and 301 single mothers. Participants were recruited through online platforms, service centers, and community networks. However, uneven regional representation and limited digital access may constrain generalizability. Research instruments included a personal information questionnaire and the Thai Family Well-Being Scale. Data were analyzed using descriptive statistics, t-tests, and multiple regression. The findings revealed very high overall family well-being in both groups, with spiritual development rated the highest, followed by educational development, while economic well-being was rated the lowest. No significant differences emerged between single-father and single-mother families. However, the factors influencing family well-being differed: for single fathers, negative predictors included work-hour patterns and obstacles to work-family balance. For single mothers, family income and help-seeking behavior were positive predictors, while work-family balance obstacles were negative predictors.